Effectiveness of Donggala Police Socialization in Preventing the Spread of Covid-19 - Wafika Nur Romadhani (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
This research aims to determine the effectiveness of the Donggala Police's socialization in preventing the spread of Covid-19 in Banawa sub-district. This type of research uses qualitative research methods which aim to produce actual data through interviews. Determining informants was carried out by purposive sampling of 7 informants to be used as samples when conducting in-depth interviews. The results of the research show that the effectiveness of the Donggala Police's socialization in preventing the spread of Covid-19 in Banawa sub-district is quite effective because the public can understand the purpose of the socialization so that it can be applied in everyday life. This research suggests that the Donggala Police should increase cooperation with related agencies in providing sanctions, not just verbal warnings, and for the community to participate in preventing the spread of Covid-19 by being disciplined in implementing health protocols, playing an active role and inviting the environment to participate in developing a culture of discipline in implementation of health protocols.